The Influence of Very Low Doses of Cisplatin on Tumor Cell Proliferation and on Some Hematological and Enzymatic Parameters of Healthy Rats - Elżbieta Malarczyk; Martyna Kandefer-Szerszeń; Anna Jarosz-Wilkołazka (SAGE Publishing, 2003)
Healthy rats had been treated for 2 or 6 weeks with 1.0 mL of 10 −8 and 10 −16 mg/mL of cisplatin. After 2 weeks of treatment, a significant increase in leukocyte and erythrocyte count and also in hematocrit was observed. Among leukocytes the number of neutrophils and eosinophils significantly increased. Biochemical analyses indicated a decrease in the glycogen content in the liver and kidneys after 2 weeks of treatment with low doses of cisplatin but at the end of the experiment (8th week of experiment) the stores of glycogen increased significantly. Biochemical analyses concerning the activity of some enzymes in the liver revealed a significant increase of peroxidase and acid phosphatase as well as catalase activities after 2 weeks of treatment. However, catalase was induced by a very low concentration of cisplatin, 10 −16 mg/mL. After the cessation of cisplatin treatment the activity of enzymes returned to normal values. Human lung carcinoma cell line A 549 (ECACC No 86012804) was also studied after treatment with the same doses of cisplatin and inhibition of its growth was observed. The results of these experiments strongly indicated that low doses of cisplatin could be stimulating for healthy cells but cytostatic for tumor cells. Possible mechanisms involved in the biological activity of very low cisplatin concentrations are discussed.